Recent development of Smart City in Japan. (3rd April 2019) - Cao, Zhejing
The energy shortage has precipitated Japan to carry out Smart City project more on Smart Community level for life quality and user respect, and converted as a prototype for overseas export. This paper aims to differentiate Japan's Smart City from global context through literature reviews and comparative analysis; formulates a comprehensive analysis framework from Japan Smart City policy, standards, to projects, based on evidences from governmental propagandas and enterprise initiatives; and give a hint on its future Smart City development. It is found that Japan's national government is the leading agent for strategic development and subsidy management, while the local government organises the consortium for stakeholders. Two waves of Smart City projects have been initiated under three goals and five approaches on smart infrastructure, energy saving and management, smart transportation, and ICT application. Stakeholder engagement, alignment to strategic urban agendas, social value, and data security should also be considered, when Smart City in Japan is evolving towards disaster resilience, tourism activation, global expansion, and international standards establishment.